Doing qualitative research - Silverman, David 1943- (London Sage, 2013)
"In the fourth edition of his best-selling textbook, David Silverman provides a step-by-step guide to planning and conducting qualitative research. Using real examples from real postgraduate students, the book makes it easy to link theory to methods and shows how to move from understanding the principles of qualitative research to doing it yourself. The new edition has been fully updated and now includes: a brand new chapter on formulating a research question appropriate for qualitative research - an expanded discussion of the role of theory in research - extended discussion of case study research and the number of cases needed for effective qualitative research - further coverage of focus groups and analyzing internet data - new student examples from around the world - a new section on the common pitfalls encountered in qualitative research - an expanded companion website with more student examples and videos. Filled with exercises to test your understanding and develop your skills, as well as David's own tips for research success based on years of experience, this book is essential reading for anyone doing qualitative research."--Publisher's website.
Preface to the Fourth Edition -- Companion Website -- Part 1: Introduction. How to Use This Book ; What You Can (and Can't) Do with Qualitative Research ; Focusing Research Project ; Issues in Research Design ; What Counts as 'Originality'?. -- Part 2: Starting Out. Formulating a Research Question ; Using Theories ; Choosing a Methodology ; How Many Cases Do You Need? ; Ethical Research ; Writing a Research Proposal. -- Part 3: Collecting and analyzing your data. Collecting Your Data ; Developing Data Analysis ; Using Computers to Analyse Qualitative Data Clive Seale ; Quality in Qualitative Research ; Evaluating Qualitative Research ; Effective Qualitative Research. -- Part 4: Writing up. The First Few Pages ; The Literature Review Chapter ; The Methodology Chapter ; Writing Your Data Chapters ; Your Concluding Chapter. -- Part 5: Getting support. Making Good Use of Your Supervisor ; Getting Feedback ; Surviving an Oral Examination ; Getting Published ; Audiences ; Appendix: Transcription Symbols ; Glossary ; References ; Author Index ; Subject Index.
Keywords: Qualitative research; Social sciences -- Research -- Methodology; Social sciences -- Methodology